1993
DOI: 10.1128/iai.61.6.2694-2697.1993
|View full text |Cite
|
Sign up to set email alerts
|

Iron acquisition by Helicobacter pylori: importance of human lactoferrin

Abstract: Helicobacter pylori is known to be an etiologic agent of gastritis and peptic ulcer disease in humans. However, the mechanism by which this organism acquires iron has not been studied. For this investigation, H. pylori was grown in iron-restricted medium. Siderophore production was not detected by chemical assays, and the strains were unable to use enterochelin and pyochelin for growth in low-iron media. Human lactoferrin supported full growth of the bacteria in media lacking other iron sources, but neither hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 29 publications
(21 reference statements)
2
71
0
2
Order By: Relevance
“…A predicted haemin uptake system encoded by the chu genes is also present. In contrast, a study by Husson et al (1993) concluded that H. pylori does not secrete siderophores and is unable to utilize the siderophores enterobactin and pyochelin. Although another study suggested that H. pylori does produce siderophores (Illingworth et al 1993), there are no obvious siderophore-related genes in the genome sequence of strain 26695 or J99.…”
Section: Iron Acquisitionmentioning
confidence: 94%
See 1 more Smart Citation
“…A predicted haemin uptake system encoded by the chu genes is also present. In contrast, a study by Husson et al (1993) concluded that H. pylori does not secrete siderophores and is unable to utilize the siderophores enterobactin and pyochelin. Although another study suggested that H. pylori does produce siderophores (Illingworth et al 1993), there are no obvious siderophore-related genes in the genome sequence of strain 26695 or J99.…”
Section: Iron Acquisitionmentioning
confidence: 94%
“…There is strong evidence that H. pylori is able to use human lactoferrin as the sole iron source (Husson et al 1993). This ®nding is signi®cant in view of the presence of lactoferrin in human gastric tissues, and there is evidence that lactoferrin levels are increased in patients infected with H. pylori (Nakao et al 1997).…”
Section: Iron Acquisitionmentioning
confidence: 99%
“…Though heme may be an important source of iron for the bacterium, it may have to be able to use also iron that is bound to lactoferrin. Husson et al [82] reported that H. pylori could grow using lactoferrin as the sole source of iron. Many pathogens can extract iron from lactoferrin by means of specific proteins called siderophores.…”
Section: Iron Metabolismmentioning
confidence: 99%
“…Many pathogens can extract iron from lactoferrin by means of specific proteins called siderophores. However, Husson et al [82] failed to detect extracellular siderophore production in H. pylori and suggested that the bacterium possesses a lactoferrin receptor that would allow it to extract iron directly from lactoferrin. These findings conflict with the studies of Illingworth et al [83], who reported the presence of extracellular siderophores produced by H. pylori and found no evidence of direct binding of lactoferrin by the bacterium.…”
Section: Iron Metabolismmentioning
confidence: 99%
“…First, infection with H. pylori could impair iron uptake because the infection is mostly accompanied by gastric hypoacidity; 9 and second, H. pylori infection could increase iron demand because H. pylori requires iron for growth. 10 Although the mechanisms by which H. pylori infection might lead to iron-deficiency anemia remain unclear, a recent study ruled out gastrointestinal bleeding or iron malabsorption and suggested that H. pylori gastritis could act as a sequestering focus for iron. 1 Nakao et al reported that lactoferrin concentration increased in the gastric juice and biopsy specimens of patients with H. pylori-related gastritis, and that the levels of lactoferrin correlate significantly with the degree of inflammation of the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%